Pelaksanaan Senam Hamil Sebagai Upaya Mempersiapkan Persalinan Di Klinik Nining Ka. Asahan - Herviza Wulandary Pane; Gunarmi; Eka Vicky Yulivantina (Cv. Utility Project Solution, 2022)
Pregnancy exercise during pregnancy can increase birth weight and reduce the incidence of premature and labor complications according to Narendran (2009) in Bangalore. While the benefits of regular pregnancy exercise are very helpful in maintaining health and the smooth delivery and postpartum process because pregnancy exercise will make the body flexible, especially in the muscles of the birth canal. This muscle flexibility is very necessary because when facing childbirth, mothers are usually hit by anxiety and panic. The method used in increasing this knowledge is by providing counseling in the form of interactive lectures and giving leaflets to the participants who are present. The material is given by interactive discussion method. Participants looked enthusiastic listening to the material presented by the instructor. The question-and-answer session was opened after the four instructors finished delivering the material. At the end of the activity, after the counseling, the practice of pregnancy exercise was continued and participants were required to follow the overall movements taught, and it can be concluded that all pregnant women had increased their knowledge about pregnancy exercise, and they were also very enthusiastic about practicing every movement taught during pregnancy exercise.